The Relationship between TQM, EO and Business Performance of SMEs: Mediating Role of Market Orientation - Jabeen, Rubina; Mahmood, Rosli (UUM Press, 2014)
Unprecedented challenges have become more intense in today’s globalized economy. The firms, that provide quality and innovative products, focus on cost reduction, emphasize on increased customer satisfaction, can survive and prosper well, and can exceed the other firms. Small and medium enterprises (SMEs) have been regarded as a back bone of the financial system of any country. Role of SMEs has become even more significant in developing countries like Pakistan, where more than 90 % enterprises are SMEs, but their dismal performance is a key issue today. Total quality management (TQM), entrepreneurial orientation (EO) and market orientation are important business strategies that can enhance the performance of SMEs. The aim of this paper is to examine the mediating effect of market orientation on the relationship between total quality management, entrepreneurial orientation and business performance of SMEs in Pakistan. On the basis of a thorough literature review, the research model is proposed and four research hypotheses have been presented. Questionnaire protocol was used to collect the data from owner/managers of SMEs and SPSS was employed to test the hypotheses. The findings revealed that significant relationship exist between total quality management and business performance, while market orientation was found to mediate the total quality management and business performance relationship and entrepreneurial orientation and business performance relationship respectively. This paper provides an insightful contribution for better understanding of owner/managers of SMEs to adopt business strategies to survive the intensely competitive market environment and develop a competitive edge.